Interrelation between Ecology and Inflation: Theoretical and Institutional Aspect - D. I. Ramazanov (Вестник Российского экономического университета имени Г. В. Плеханова)
The article studies the issue of inflation and ecology in theoretical and institutional aspect. We realize the importance of classical factors of inflation, however we would like to highlight such factor as ecology, to be more precise, expenses on providing ecological well-being. In the near future global expenses on ecology can become a considerable reason for price rise. The contribution of ecological well-being to inflation was analyzed from theoretical point of view. The article also explains the mechanism of green inflation development: a growth in nonproduction spending on nature protection at the current stage of output can cause cost rising on average per unit of product. Interrelation between ecology and inflation is shown as a modified Kuznets ecological curve. The graph shows that inflation decreases with rising environmental pollution, but to a certain crucial moment, after which inflation starts growing. The author gives arguments to support the modified Kuznets ecological curve, the major one is the fact that the lower nature-protection costs of the producer that means a high level of pollution, the lower production costs are and thus the lower inflation is and visa verse. The author analyzed results of sociological research that demonstrated that customers are not ready to pay for ecology improvement and price regulation mechanism does not work in this case. In the institutional aspect the fact that price mechanism cannot be used was proved by using the problem of ‘free-rider’ and information asymmetry in regard to ecological well-being as public wealth, which could lead to adverse effects. Certain non-market solutions of the problem of ecology and inflation were proposed.